2017
DOI: 10.1002/ajmg.c.31591
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and genotype analysis of a French cohort of 119 patients with CHARGE syndrome

Abstract: International audienceCHARGE syndrome (CS) is a genetic disorder whose first description included Coloboma, Heart disease, Atresia of choanae, Retarded growth and development, Genital hypoplasia, and Ear anomalies and deafness, most often caused by a genetic mutation in the CHD7 gene. Two features were then added: semicircular canal anomalies and arhinencephaly/olfactory bulb agenesis, with classification of typical, partial, or atypical forms on the basis of major and minor clinical criteria. The detection ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 24 publications
4
89
0
1
Order By: Relevance
“…Among postnatal criteria for CS, our study confirms that arhinencephaly (ARh) and semicircular canal agenesis (SCA) can be observed prenatally in the vast majority of cases, as they were present in 100% and 92.3% of cases, respectively, corroborating recent literature . MRI demonstrates a high rate of detection of both criteria (100%), whereas ultrasound tends to be less sensitive (ARh, 38.4%; SCA, 33.3%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among postnatal criteria for CS, our study confirms that arhinencephaly (ARh) and semicircular canal agenesis (SCA) can be observed prenatally in the vast majority of cases, as they were present in 100% and 92.3% of cases, respectively, corroborating recent literature . MRI demonstrates a high rate of detection of both criteria (100%), whereas ultrasound tends to be less sensitive (ARh, 38.4%; SCA, 33.3%).…”
Section: Discussionsupporting
confidence: 88%
“…Isolated or multiple congenital anomalies were only detected in 58% of the pregnancies. The most recent study of Legendre et al reported an estimated incidence of detected prenatal anomalies in 46.6% in their 116 postnatal cases. The most frequent isolated features were described by ultrasonography and included heart defects, cleft lip and palate, polyhydramnios, and growth restriction.…”
Section: Introductionmentioning
confidence: 96%
“…Given the range of pathogenic variants seen in CHARGE syndrome (Moccia et al, ; Zentner et al, ), it is important to understand the impact of causative CHD7 variants on the CHARGE syndrome cardiac phenotype. Within the spectrum of CHD in CHARGE syndrome, there appears to be no significant difference in presence of CHD in patients with or without a CHD7 pathogenic variant (Bergman et al, ; Corsten‐Janssen, Kerstjens‐Frederikse, et al, ; Corsten‐Janssen, Saitta, et al, ; Hale et al, ; Legendre et al, ; Vissers et al, ; Zentner et al, ). However, some larger series suggest an increase in congenital heart disease in CHD7 ‐positive patients (66–92%) compared to 71% of CHD7 ‐negative patients (Jongmans et al, ; Jyonouchi, McDonald‐McGinn, Bale, Zackai, & Sullivan, ; Lalani et al, ).…”
Section: Patterns Of Congenital Heart Disease In Chargementioning
confidence: 99%
“…The primary limitation of these data to detect more detailed genotype–phenotype relationships is the sample size in individual studies. The growing repository of large cohort studies that collect the cardiac phenotype and presence of CHD7 variant or CHD7 variant type (truncating or nontruncating; Corsten‐Janssen, Kerstjens‐Frederikse, et al, ; Corsten‐Janssen, Saitta, et al, ; Jongmans et al, ; Lalani et al, ; Legendre et al, ; Vissers et al, ; Wincent et al, ) should allow for pooling of these large datasets for more detailed meta‐analysis. However, the overlap of pathogenic variant data and congenital heart defect phenotype is not routinely presented in most studies, which prevents data aggregation and meta‐analysis and argues for publication of supplemental datasets including this information.…”
Section: Patterns Of Congenital Heart Disease In Chargementioning
confidence: 99%
See 1 more Smart Citation